Detection of Some Foodborne Pathogens In Some Food Samples Using Species - Specific Polymerase Chain Reaction Technique - Hamasaleh, Sakar kamal; Hassan, Khulod Ibraheem (Sulaimani Journal for Pure and Applied Sciences, 2018)
Polymerase Chain Reaction (PCR) techniques was applied as a rapid method for detection of some food-borne pathogens directly without culturing, to detect three species of bacteria, including: Shigella flexneri, Escherichia coli 0157:H7 and Listeria monocytogenese by targeting specific genes for each pathogen from cultures of various types of artificially inoculated foods, which were spiked with reference bacteria at known concentrations. DNA was isolated from each food sample using phenol -chloroform based method.Positive results were obtained which produced specific amplicons of the expected sizes of each of them (691 bp in L. monocytogenese, 556 bp in E.coli o157:H7 and 600 bp in S. flexneri). The detection limit of the assay were 103 CFU/ ml For L. monocytogenese, and 104 CFU/ ml for both S. flexneri and E.coli o157:H7. overall results of this study indicate that PCR is a good tool for rapid screening of the three pathogens in food and this application can be followed for detection of any pathogenic bacteria transmitted through food.
Keywords: PCR; food; Shigella flexner; Escherichia coli 0157; Listeria monocytogenese